Development of WebGIS-Based Monitoring System for Key Performance Indicators of Muhammadiyah Regional Board in Central Java - Jumadi; Handaga, Bana; Nugroho, Munajat Tri; Dai, Muhammad; Ariyanto, Gunawan; Nurgiyatna (Journal of Community Services and Engagement: Voice of Community (VOC), 2024)
This paper aims to describe the development of a WebGIS application for the Muhammadiyah Regional Board of Central Java as a monitoring tool for the organization's Key Performance Indicator. The initial phase of the project involved conducting Focus Group Discussions (FGDs) to collect data regarding the organization's needs and requirements. Furthermore, the design process involved creating a comprehensive inventory of application functions and user interfaces. The use of WebGIS technology enables monitoring of key performance indicators (KPIs) and integration of spatial data. This enables more comprehensive visualization of performance data through interactive dashboards and spatial visualization. Further enhancements to the application were designed based on a thorough stakeholder review, taking into account comments obtained through the stakeholder review process. Once the application reached a satisfactory level of performance, it was formally introduced to stakeholders through a socialization process. The application was started and its security was verified using the reliable hypertext transfer protocol (HTTPS) via the URL https://kpi.pwmjateng.id. The implementation of the KPI monitoring tool based on WebGIS technology has yielded good results, and it is showing its success within the Muhammadiyah Regional Board of Central Java. Now, they can effectively monitor and track their indicators.